Effective Cleaving Parameters for Multimode Gradient Index CYTOP Polymer Fiber - Chapalo, Ivan E.; Theodosiou, Antreas; Pobegalov, Georgii; Chapalo, Sergei; Kalli, Kyriacos; Kotov, Oleg I. (My University, 2020)
We experimentally address simple, low-cost and effective methods for the cleaving of multimode CYTOP optical fibers using razor blades. The quality of fiber end-face preparation depends on various parameters. The necessity of the near-field intensity pattern inspection for adequate evaluation of cleaved fiber end-faces is demonstrated. Razor blades of different manufacturers are evaluated for manual cleaving, as well as automated cleaving with controlled speed and temperature. The cleaving technique with both slowed motion of the razor blade and increased temperature up to 90 °C demonstrated the best quality of fiber end-faces. Typical cleaving defects are highlighted, whereas the cleave quality was characterized in terms of the light intensity profile emitted by the fiber in near field.
Keywords: CYTOP; Fiber cleave; Fiber optics; Multimode fiber; Polymer optical fiber